Waterborne polyurethane grafted sericin composite nanofiber membrane based on electrostatic spinning and preparation method of waterborne polyurethane grafted sericin composite nanofiber membrane
The preparation of aqueous polyurethane grafted sericin composite nanofiber membrane through electrospinning technology solved the problem of no improvement in mechanical properties, decreased stability and worsening of biocompatibility when sericin is compounded with synthetic polymers, and achieved high Sericin composite nanofiber membrane with mechanical properties and good biocompatibility.
Patent Information
- Application Number
- CN202411518520.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
When sericin is combined with synthetic polymer electrospin, the mechanical properties are not significantly improved, stability is reduced, and biocompatibility is worse.
The aqueous polyurethane grafted sericin composite nanofiber membrane was prepared by electrospinning technology. By emulsifying the sericin solution with the aqueous polyurethane, an aqueous polyurethane grafted sericin emulsion was formed and blended with polycaprolactone for electrostatic electricity. Spinning, ultimately treated under ethanol steam to improve mechanical properties and biocompatibility.
It significantly improves the mechanical properties and biocompatibility of sericin, improves the stability and moisture permeability of composite nanofiber membranes, making it suitable for applications requiring high mechanical properties and good biocompatibility.
Smart Images

Figure BDA0005107389770000121 
Figure BDA0005107389770000122
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrospun fiber membrane technology, and in particular to an electrospun aqueous polyurethane-grafted sericin composite nanofiber membrane and its preparation method. Background Technology
[0002] Sericin is a water-soluble, natural, high-molecular-weight globular protein composed of 18 amino acids, including serine and aspartic acid. It possesses excellent hydrophilicity, chemical activity, and skin-moisturizing, antioxidant, and biocompatibility properties. However, electrospun nanofibers obtained directly from pure sericin suffer from poor mechanical strength and easy degradation due to their high water solubility and lack of intermolecular and intramolecular cross-linking, rendering them impractical. Therefore, the preparation of sericin composite materials is an inevitable trend for improving the practical performance of sericin fiber materials.
[0003] To improve the properties of sericin nanofibers, extensive research has been conducted on the electrospinning of sericin in combination with other materials. For example, natural polymers (such as silk fibroin, chitosan, elastin, and hyaluronic acid) are combined with sericin for blend spinning. Natural polymers, derived from plants and animals, have good biocompatibility, and their natural biological structures are not found in synthetic polymers; however, many natural polymers are polyelectrolytes, making electrospinning them more difficult than with synthetic polymers. Alternatively, synthetic polymers can be blended with sericin. While synthetic polymers are easier to obtain electrospun products from, the differences in physical and chemical properties between synthetic polymers and sericin can lead to mixed films exhibiting poor stability, lower strength, and toughness. Furthermore, some synthetic polymers (such as polylactic acid) produce acidic substances during degradation, lacking good biocompatibility, which limits the application of sericin-synthetic polymer blends in specific fields.
[0004] Therefore, how to provide a sericin composite electrospun product with excellent stability, good moisture permeability, high mechanical properties and better biocompatibility is an important research direction in this field. Summary of the Invention
[0005] The purpose of this invention is to provide an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning and its preparation method, which solves the problems of no significant improvement in mechanical properties, decreased stability, and poor biocompatibility that exist when sericin is combined with synthetic polymers through electrospinning.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0007] This invention provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, comprising the following steps:
[0008] (1) Polypropylene glycol, dimethylolpropionic acid, isophorone diisocyanate and stannous octoate are mixed and subjected to a first reaction; the mixture is cooled and triethylamine is added for a neutralization reaction; then water is added for a first emulsification to obtain waterborne polyurethane; a sericin solution is added to the waterborne polyurethane for a second emulsification to obtain a waterborne polyurethane grafted sericin emulsion.
[0009] (2) Polycaprolactone, waterborne polyurethane grafted sericin emulsion and hexafluoroisopropanol are mixed to obtain a spinning solution; the spinning solution is electrospun to obtain a composite nanofiber membrane to be treated.
[0010] (3) The composite nanofiber membrane to be treated was treated under ethanol vapor to obtain an aqueous polyurethane grafted sericin composite nanofiber membrane.
[0011] The preparation method of the sericin solution in step (1) includes the following steps:
[0012] The broken silkworm cocoons were mixed with anhydrous sodium carbonate solution and degummed to obtain a precursor solution; the precursor solution was dialyzed to obtain sericin; the sericin was mixed with water to obtain a sericin solution.
[0013] In step (1), the rotation speed of the first emulsification is 6000-10000 r / min and the time is 2-4 min; in step (1), the rotation speed of the second emulsification is 4000-6000 r / min and the time is 1-2 h.
[0014] Preferably, in the method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, step (1) includes the following raw materials in parts by weight: 30-60 parts polypropylene glycol, 2-5 parts dimethylolpropionic acid, 20-36 parts isophorone diisocyanate, 0.1-0.3 parts stannous octoate, 0.5-3 parts triethylamine, 100-200 parts water, and 75-150 parts sericin solution; the concentration of the sericin solution in step (1) is 15-25 wt.%.
[0015] Preferably, in the method for preparing an aqueous polyurethane grafted sericin composite nanofiber membrane based on electrospinning, the temperature of the first reaction in step (1) is 75-85°C and the time is 2.5-5h; the temperature of the neutralization reaction in step (1) is 35-40°C and the time is 0.8-1.6h.
[0016] Preferably, in the method for preparing an aqueous polyurethane grafted sericin composite nanofiber membrane based on electrospinning, the solid content of the aqueous polyurethane grafted sericin emulsion in step (1) is 20-45%.
[0017] Preferably, in the method for preparing an electrospun aqueous polyurethane-grafted sericin composite nanofiber membrane, the preparation method of polycaprolactone in step (2) includes the following steps:
[0018] Tetrahydrofuran, a small molecule monohydric alcohol, a diphenyl phosphate solution, and caprolactone were mixed and polymerized under a protective atmosphere to obtain polycaprolactone.
[0019] Preferably, in the method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, the small molecule monohydric alcohol is n-propanol or n-butanol.
[0020] Preferably, in the method for preparing an aqueous polyurethane grafted sericin composite nanofiber membrane based on electrospinning, the mass-volume ratio of polycaprolactone, aqueous polyurethane grafted sericin emulsion and hexafluoroisopropanol in step (2) is 1g:5-12g:20mL.
[0021] Preferably, in the method for preparing an aqueous polyurethane grafted sericin composite nanofiber membrane based on electrospinning, the electrospinning parameters in step (2) are: receiving distance of 15-20 cm, needle hole inner diameter of 0.8-1.2 mm, solution flow rate of 0.4-0.6 mL / h, and voltage of 15-20 kV.
[0022] Preferably, in the method for preparing an aqueous polyurethane grafted sericin composite nanofiber membrane based on electrospinning, the treatment time under ethanol vapor in step (3) is 0.4 to 1 hour, and the concentration of ethanol vapor in step (3) is 70 to 85 wt.%.
[0023] The present invention also provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, thereby obtaining an aqueous polyurethane-grafted sericin composite nanofiber membrane.
[0024] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) Waterborne polyurethanes typically contain unreacted isocyanate groups (-NCO), which can react with amino groups (-NH2) to form amide bonds (-NH-CO-). Sericin contains a large number of hydrophilic side chain groups such as hydroxyl, carboxyl, and amino groups, which can react with waterborne polyurethanes. However, directly using sericin as a synthetic material in the synthesis of waterborne polyurethanes can easily lead to unstable overall performance of the waterborne polyurethanes. In this invention, sericin is added to the emulsified waterborne polyurethane. Since sericin is obtained through alkaline hydrolysis of silkworm cocoons, it effectively reduces the molecular weight of sericin. Furthermore, because sericin is decomposed into smaller peptides or amino acids, the number of amino groups carried by sericin is increased, which greatly improves the grafting effect between sericin and waterborne polyurethane. This allows sericin to be grafted onto waterborne polyurethane while retaining its good moisture permeability and biocompatibility, thereby improving the mechanical properties of sericin. Furthermore, the present invention further emulsifies the mixture of sericin and aqueous polyurethane to form tiny droplets containing the two materials, increasing the contact area between them, which is more conducive to the grafting reaction and ensures the stability of the grafted product of sericin and aqueous polyurethane.
[0026] (2) Polycaprolactone is a biodegradable synthetic polymer material with good biocompatibility and biodegradability, and excellent mechanical properties. This invention involves electrospinning a blend of polycaprolactone and sericin grafted with waterborne polyurethane. Polycaprolactone can serve as a reinforcing component in the composite nanofiber membrane, effectively improving the mechanical properties of sericin and enhancing its processing performance. By combining the advantages of both materials, a sericin composite nanofiber membrane material with good biocompatibility, moisture permeability, and excellent mechanical properties is obtained, making the composite nanofiber membrane more durable and stable.
[0027] (3) The present invention also incorporates an ethanol vapor post-treatment process. The hydroxyl groups (-OH) in ethanol can form hydrogen bonds with the hydrophilic groups on sericin, changing the intermolecular interaction forces of sericin molecules and causing them to change from a hydrophilic state to a hydrophobic state. At the same time, ethanol molecules can also penetrate between the molecular chains of sericin, destroying its original hydration layer and further reducing its water solubility, thereby generating a sericin composite nanofiber membrane that is not easily soluble in water and has good mechanical properties, and finally obtaining a sericin composite nanofiber membrane with good biocompatibility, strong air and moisture permeability and excellent mechanical properties. Detailed Implementation
[0028] This invention provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, comprising the following steps:
[0029] (1) Polypropylene glycol, dimethylolpropionic acid, isophorone diisocyanate and stannous octoate are mixed and subjected to a first reaction; the mixture is cooled and triethylamine is added for a neutralization reaction; then water is added for a first emulsification to obtain waterborne polyurethane; a sericin solution is added to the waterborne polyurethane for a second emulsification to obtain a waterborne polyurethane grafted sericin emulsion.
[0030] (2) Polycaprolactone, waterborne polyurethane grafted sericin emulsion and hexafluoroisopropanol are mixed to obtain a spinning solution; the spinning solution is electrospun to obtain a composite nanofiber membrane to be treated.
[0031] (3) The composite nanofiber membrane to be treated was treated under ethanol vapor to obtain an aqueous polyurethane grafted sericin composite nanofiber membrane.
[0032] In this invention, the molecular weight of the polypropylene glycol in step (1) is preferably 1000-2000, more preferably 1500-2000, and even more preferably 2000.
[0033] In this invention, step (1) preferably includes the following raw materials in parts by weight: 30-60 parts polypropylene glycol, 2-5 parts dimethylolpropionic acid, 20-36 parts isophorone diisocyanate, 0.1-0.3 parts stannous octoate, 0.5-3 parts triethylamine, 100-200 parts water, and 75-150 parts sericin solution;
[0034] Further preferred formulations include: 45-50 parts polypropylene glycol, 2-3 parts dimethylolpropionic acid, 20-25 parts isophorone diisocyanate, 0.1-0.2 parts stannous octoate, 0.5-2 parts triethylamine, 100-150 parts water, and 80-120 parts sericin solution.
[0035] More preferably, it contains: 45 parts polypropylene glycol, 3 parts dimethylolpropionic acid, 25 parts isophorone diisocyanate, 0.2 parts stannous octoate, 2 parts triethylamine, 150 parts water, and 120 parts sericin solution.
[0036] In this invention, the preferred method for mixing polypropylene glycol, dimethylolpropionic acid, isophorone diisocyanate and stannous octoate in step (1) is as follows: the polypropylene glycol and dimethylolpropionic acid are mixed and heated to 100-120°C (more preferably 100-110°C, more preferably 100°C), and kept at that temperature for 1-2 hours (more preferably 1-1.5 hours, more preferably 1 hour); then the temperature is lowered to 40-60°C (more preferably 50-60°C, more preferably 60°C), and isophorone diisocyanate and stannous octoate are added and mixed.
[0037] In this invention, the temperature of the first reaction in step (1) is preferably 75-85°C, more preferably 75-80°C, and even more preferably 80°C; the time is preferably 2.5-5h, more preferably 2.5-4h, and even more preferably 4h.
[0038] In this invention, the temperature of the neutralization reaction in step (1) is preferably 35-40°C, more preferably 35-38°C, and even more preferably 35°C; the time is preferably 0.8-1.6h, more preferably 0.8-1.2h, and even more preferably 1.2h.
[0039] In this invention, the rotation speed of the first emulsification in step (1) is preferably 6000-10000 r / min, more preferably 7500-10000 r / min, and even more preferably 10000 r / min; the time is preferably 2-4 min, more preferably 2-3 min, and even more preferably 3 min.
[0040] In this invention, the method for preparing the sericin solution in step (1) preferably includes the following steps:
[0041] The broken silkworm cocoons were mixed with anhydrous sodium carbonate solution and degummed to obtain a precursor solution; the precursor solution was dialyzed to obtain sericin; the sericin was mixed with water to obtain a sericin solution.
[0042] In this invention, the concentration of the anhydrous sodium carbonate solution is preferably 4-8 wt.%, more preferably 4-6 wt.%, and even more preferably 6 wt.%.
[0043] In this invention, the mass ratio of the silkworm cocoon to the anhydrous sodium carbonate solution is preferably 1:40-50, more preferably 1:45-50, and even more preferably 1:50.
[0044] In this invention, the degumming process preferably also includes continuous dispersion.
[0045] In this invention, the degumming temperature is preferably 90-100°C, more preferably 95-100°C, and even more preferably 100°C; the degumming time is preferably 0.5-1h, more preferably 0.8-1h, and even more preferably 0.8h.
[0046] In this invention, the molecular weight cutoff for dialysis is preferably 6-15 kD, more preferably 12-15 kD, and even more preferably 12 kD.
[0047] In this invention, the preferred method of dialysis is to place the precursor solution into a dialysis bag, dialyze with running water for 2 to 4 days (more preferably 3 to 4 days, more preferably 4 days), and then dialyze with deionized water for 1 to 2 days (more preferably 1 to 1.5 days, more preferably 1 day).
[0048] In this invention, the dialysis process preferably further includes the following steps: sequential filtration, anhydrous ethanol filtration, and drying. This invention does not limit the conditions for the sequential filtration, filtration, and drying; any method well-known to those skilled in the art can be used.
[0049] In this invention, the concentration of the sericin solution in step (1) is preferably 15-25 wt.%, more preferably 20-25 wt.%, and even more preferably 20 wt.%.
[0050] In this invention, the rotation speed of the second emulsification in step (1) is preferably 4000-6000 r / min, more preferably 5000-6000 r / min, and even more preferably 6000 r / min; the time is preferably 1-2 h, more preferably 1.6-2 h, and even more preferably 2 h.
[0051] In this invention, the solid content of the waterborne polyurethane grafted sericin emulsion in step (1) is preferably 20-45%, more preferably 25-31%, and even more preferably 28%.
[0052] In this invention, the method for preparing polycaprolactone in step (2) preferably includes the following steps:
[0053] Tetrahydrofuran, a small molecule monohydric alcohol, a diphenyl phosphate solution, and caprolactone were mixed and polymerized under a protective atmosphere to obtain polycaprolactone.
[0054] In this invention, the small molecule monohydric alcohol is preferably n-propanol or n-butanol, and more preferably n-butanol.
[0055] In this invention, the diphenyl phosphate solution is preferably a mixed solution of diphenyl phosphate and tetrahydrofuran.
[0056] In this invention, the concentration of the diphenyl phosphate solution is preferably 1-2 mol / L, more preferably 1.5-2 mol / L, and even more preferably 1.5 mol / L.
[0057] In this invention, the molar ratio of the small molecule monohydric alcohol, the diphenyl phosphate in the diphenyl phosphate solution, and the caprolactone is preferably 0.8-1.2:1:25-30, more preferably 0.8-1:1:28-30, and even more preferably 1:1:30.
[0058] In this invention, the molar volume ratio of caprolactone to tetrahydrofuran is preferably 1.5-2 mol:1 L, more preferably 1.8-2 mol:1 L, and even more preferably 2 mol:1 L.
[0059] In this invention, the small molecule monohydric alcohol and the caprolactone are preferably prepared by dissolving the small molecule monohydric alcohol and the caprolactone separately in tetrahydrofuran before adding them to the mixed system.
[0060] In this invention, the protective atmosphere is preferably argon.
[0061] In this invention, the temperature of the polymerization reaction is preferably 20-25°C, more preferably 20-22°C, and even more preferably 20°C; the time is preferably 15-20h, more preferably 15-18h, and even more preferably 18h.
[0062] In this invention, a post-processing step is preferably included after the polymerization reaction. Specifically, the product obtained from the polymerization reaction is mixed with dichloromethane, purified by precipitation with cold methanol, and filtered to obtain polycaprolactone.
[0063] The present invention does not limit the parameters in the post-processing, and any solution known to those skilled in the art can be used.
[0064] In this invention, the mass-to-volume ratio of polycaprolactone, aqueous polyurethane grafted silk protein emulsion and hexafluoroisopropanol in step (2) is preferably 1g:5-12g:20mL, more preferably 1g:6.5-10g:20mL, and even more preferably 1g:10g:20mL.
[0065] In this invention, the mixing temperature in step (2) is preferably 15-25°C, more preferably 20-25°C, and even more preferably 20°C; the mixing time is preferably 10-15h, more preferably 10-12h, and even more preferably 12h.
[0066] In this invention, the preferred parameters for electrospinning in step (2) are: receiving distance of 15-20 cm, needle hole inner diameter of 0.8-1.2 mm, solution flow rate of 0.4-0.6 mL / h, and voltage of 15-20 kV; more preferably: receiving distance of 18-20 cm, needle hole inner diameter of 0.8-1 mm, solution flow rate of 0.4-0.5 mL / h, and voltage of 18-20 kV; and even more preferably: receiving distance of 18 cm, needle hole inner diameter of 1 mm, solution flow rate of 0.5 mL / h, and voltage of 20 kV.
[0067] In this invention, the concentration of ethanol vapor in step (3) is preferably 70-85 wt.%, more preferably 70-80 wt.%, and even more preferably 70 wt.%.
[0068] In this invention, the treatment time under ethanol vapor in step (3) is preferably 0.4 to 1 hour, more preferably 0.8 to 1 hour, and even more preferably 1 hour.
[0069] The present invention also provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, thereby obtaining an aqueous polyurethane-grafted sericin composite nanofiber membrane.
[0070] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0071] Example 1
[0072] This embodiment provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, comprising the following steps:
[0073] (1) Preparation of sericin solution: The broken silkworm cocoons were mixed with an anhydrous sodium carbonate solution with a concentration of 6 wt.% at a mass ratio of 1:50. The mixture was degummed at 100℃ and continuously stirred for 0.8 h to obtain a precursor solution. The precursor solution was placed in a dialysis bag with a molecular weight cutoff of 12 kD. The mixture was dialyzed with running water for 4 days, then dialyzed with deionized water for 2 days. The mixture was then filtered, filtered with anhydrous ethanol, and dried to obtain sericin. The sericin was mixed with water to obtain a sericin solution with a concentration of 20 wt.%.
[0074] Preparation of polycaprolactone: A tetrahydrofuran solution of n-butanol, a tetrahydrofuran solution of diphenyl phosphate (1.5 mol / L), a tetrahydrofuran solution of caprolactone, and tetrahydrofuran were mixed. The molar ratio of n-butanol, diphenyl phosphate, and caprolactone was 1:1:30, and the ratio of caprolactone to tetrahydrofuran in the mixed system was 2 mol:1 L. The mixture was reacted at 20 °C for 18 h under argon protection. The resulting product was mixed with dichloromethane, purified by precipitation with cold methanol, and filtered to obtain polycaprolactone.
[0075] (2) Mix 45 parts of polypropylene glycol PPG 2000 with 3 parts of dimethylolpropionic acid and heat to 100°C, keep warm for 1 hour; then cool down to 60°C, add 25 parts of isophorone diisocyanate and 0.2 parts of stannous octoate, and react at 80°C for 4 hours; cool down to 35°C, add 2 parts of triethylamine and react for 1.2 hours; add 150 parts of water and emulsify at 10000 r / min for 3 minutes to obtain waterborne polyurethane; add 120 parts of sericin solution to the waterborne polyurethane and emulsify at 6000 r / min for 2 hours to obtain waterborne polyurethane grafted sericin emulsion with a solid content of 28%;
[0076] (3) Polycaprolactone, waterborne polyurethane grafted sericin emulsion and hexafluoroisopropanol were mixed at 20°C for 12 h in a ratio of 1 g: 10 g: 20 mL to obtain a spinning solution; the spinning solution was electrospun, and the electrospinning parameters were set as follows: receiving distance 18 cm, needle hole inner diameter 1 mm, solution flow rate 0.5 mL / h, voltage 20 kV to obtain the composite nanofiber membrane to be treated;
[0077] (4) The composite nanofiber membrane to be treated was treated with 70 wt.% ethanol vapor for 1 h to obtain an aqueous polyurethane grafted sericin composite nanofiber membrane.
[0078] Example 2
[0079] This embodiment provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, comprising the following steps:
[0080] (1) Preparation of sericin solution: The broken silkworm cocoons were mixed with an anhydrous sodium carbonate solution with a concentration of 4 wt.% at a mass ratio of 1:50. The mixture was degummed at 100℃ and continuously stirred for 1 h to obtain a precursor solution. The precursor solution was placed in a dialysis bag with a molecular weight cutoff of 15 kD. The mixture was dialyzed with running water for 4 days, then dialyzed with deionized water for 1 day. The mixture was then filtered, filtered with anhydrous ethanol, and dried to obtain sericin. The sericin was mixed with water to obtain a sericin solution with a concentration of 25 wt.%.
[0081] Preparation of polycaprolactone: A tetrahydrofuran solution of n-butanol, a tetrahydrofuran solution of diphenyl phosphate (1.5 mol / L), a tetrahydrofuran solution of caprolactone, and tetrahydrofuran were mixed. The molar ratio of n-butanol, diphenyl phosphate, and caprolactone was 0.8:1:25, and the ratio of caprolactone to tetrahydrofuran in the mixed system was 1.5 mol:1 L. The mixture was reacted at 25 °C for 15 h under argon protection. The resulting product was mixed with dichloromethane, purified by precipitation with cold methanol, and filtered to obtain polycaprolactone.
[0082] (2) Mix 30 parts of polypropylene glycol PPG 1000 with 2 parts of dimethylolpropionic acid and heat to 100°C, keep warm for 1 hour; then cool down to 40°C, add 20 parts of isophorone diisocyanate and 0.1 parts of stannous octoate, and react at 75°C for 2.5 hours; cool down to 35°C, add 0.5 parts of triethylamine and react for 0.8 hours; add 100 parts of water and emulsify at 10,000 r / min for 2 minutes to obtain waterborne polyurethane; add 80 parts of sericin solution to the waterborne polyurethane and emulsify at 4,000 r / min for 2 hours to obtain waterborne polyurethane grafted sericin emulsion with a solid content of 31%;
[0083] (3) Polycaprolactone, waterborne polyurethane grafted sericin emulsion and hexafluoroisopropanol were mixed at 15°C for 10 h to obtain a spinning solution; the spinning solution was electrospun, and the electrospinning parameters were set as follows: receiving distance 20 cm, needle hole inner diameter 0.8 mm, solution flow rate 0.4 mL / h, voltage 15 kV to obtain the composite nanofiber membrane to be treated;
[0084] (4) The composite nanofiber membrane to be treated was treated with ethanol vapor at a concentration of 85 wt.% for 0.5 h to obtain an aqueous polyurethane grafted sericin composite nanofiber membrane.
[0085] Example 3
[0086] This embodiment provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, comprising the following steps:
[0087] (1) Preparation of sericin solution: The broken silkworm cocoons were mixed with an 8 wt.% anhydrous sodium carbonate solution at a mass ratio of 1:40. The mixture was degummed at 90℃ with continuous stirring for 0.5 h to obtain a precursor solution. The precursor solution was placed in a dialysis bag with a molecular weight cutoff of 8 kD. The mixture was dialyzed with running water for 2 days, then dialyzed with deionized water for 2 days. The mixture was then filtered, filtered with anhydrous ethanol, and dried to obtain sericin. The sericin was mixed with water to obtain a 15 wt.% sericin solution.
[0088] Preparation of polycaprolactone: A tetrahydrofuran solution of n-butanol, a tetrahydrofuran solution of diphenyl phosphate (1.5 mol / L), a tetrahydrofuran solution of caprolactone, and tetrahydrofuran were mixed. The molar ratio of n-butanol, diphenyl phosphate, and caprolactone was 1.2:1:25, and the ratio of caprolactone to tetrahydrofuran in the mixture was 1.8 mol:1 L. The mixture was reacted at 20 °C for 18 h under argon protection. The resulting product was mixed with dichloromethane, purified by precipitation with cold methanol, and filtered to obtain polycaprolactone.
[0089] (2) Mix 50 parts of polypropylene glycol PPG 1500 with 5 parts of dimethylolpropionic acid and heat to 110°C, keep warm for 1.5 h; then cool down to 60°C, add 30 parts of isophorone diisocyanate and 0.3 parts of stannous octoate, and react at 85°C for 5 h; cool down to 40°C, add 3 parts of triethylamine and react for 1.5 h; add 150 parts of water and emulsify at 6000 r / min for 4 min to obtain waterborne polyurethane; add 150 parts of sericin solution to waterborne polyurethane and emulsify at 5000 r / min for 2 h to obtain waterborne polyurethane grafted sericin emulsion with a solid content of 28%;
[0090] (3) Polycaprolactone, waterborne polyurethane grafted sericin emulsion and hexafluoroisopropanol were mixed at 25°C for 12 h in a ratio of 1 g: 12 g: 20 mL to obtain a spinning solution; the spinning solution was electrospun, and the electrospinning parameters were set as follows: receiving distance 15 cm, needle hole inner diameter 1.2 mm, solution flow rate 0.6 mL / h, voltage 18 kV to obtain the composite nanofiber membrane to be treated;
[0091] (4) The composite nanofiber membrane to be treated was treated with ethanol vapor at a concentration of 80 wt.% for 0.8 h to obtain an aqueous polyurethane grafted sericin composite nanofiber membrane.
[0092] Example 4
[0093] This embodiment provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning, comprising the following steps:
[0094] (1) Preparation of sericin solution: The broken silkworm cocoons were mixed with an anhydrous sodium carbonate solution with a concentration of 6 wt.% at a mass ratio of 1:45. The mixture was degummed at 95°C with continuous stirring for 1 h to obtain a precursor solution. The precursor solution was placed in a dialysis bag with a molecular weight cutoff of 10 kD. The mixture was dialyzed with running water for 3 days, then dialyzed with deionized water for 1 day. The mixture was then filtered, filtered with anhydrous ethanol, and dried to obtain sericin. The sericin was mixed with water to obtain a sericin solution with a concentration of 18 wt.%.
[0095] Preparation of polycaprolactone: A tetrahydrofuran solution of n-butanol, a tetrahydrofuran solution of diphenyl phosphate (2 mol / L), a tetrahydrofuran solution of caprolactone, and tetrahydrofuran were mixed. The molar ratio of n-butanol, diphenyl phosphate, and caprolactone was 1:1:28, and the ratio of caprolactone to tetrahydrofuran in the mixed system was 2 mol:1 L. The mixture was reacted at 20 °C for 20 h under argon protection. The resulting product was mixed with dichloromethane, purified by precipitation with cold methanol, and filtered to obtain polycaprolactone.
[0096] (2) Mix 45 parts of polypropylene glycol PPG 2000 with 4 parts of dimethylolpropionic acid and heat to 115°C, keep warm for 1.2 h; then cool down to 45°C, add 28 parts of isophorone diisocyanate and 0.2 parts of stannous octoate, and react at 80°C for 3 h; cool down to 40°C, add 2 parts of triethylamine and react for 1.2 h; add 200 parts of water and emulsify at 7500 r / min for 3 min to obtain waterborne polyurethane; add 100 parts of sericin solution to waterborne polyurethane and emulsify at 5500 r / min for 1.6 h to obtain waterborne polyurethane grafted sericin emulsion with a solid content of 25%;
[0097] (3) Polycaprolactone, waterborne polyurethane grafted sericin emulsion and hexafluoroisopropanol were mixed at 20°C for 12 h in a ratio of 1 g: 8 g: 20 mL to obtain a spinning solution; the spinning solution was electrospun, and the electrospinning parameters were set as follows: receiving distance 18 cm, needle hole inner diameter 1 mm, solution flow rate 0.6 mL / h, voltage 20 kV to obtain the composite nanofiber membrane to be treated.
[0098] (4) The composite nanofiber membrane to be treated was treated with 75 wt.% ethanol vapor for 0.6 h to obtain an aqueous polyurethane grafted sericin composite nanofiber membrane.
[0099] Comparative Example 1
[0100] This comparative example provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning. The difference from Example 1 is that the polycaprolactone-related schemes in steps (1) and (3) are deleted, while other parameters and conditions are the same as in Example 1.
[0101] Comparative Example 2
[0102] This comparative example provides a method for preparing a sericin composite nanofiber membrane based on electrospinning. The difference from Example 1 is that step (2) is deleted, and the ratio of polycaprolactone, sericin solution and hexafluoroisopropanol in step (3) is modified to 1g:3.4g:20mL. Other parameters and conditions are the same as in Example 1.
[0103] Comparative Example 3
[0104] This comparative example provides a method for preparing an aqueous polyurethane-grafted sericin composite nanofiber membrane based on electrospinning. The difference from Example 1 is that step (4) is deleted, while other parameters and conditions are the same as in Example 1.
[0105] Water absorption test: A 5cm × 5cm nanofiber membrane sample was immersed in deionized water and placed in a constant temperature incubator at 37℃ overnight. After removing the nanofiber membrane, the surface moisture was blotted dry with filter paper and then weighed (W). sThen, the nanofiber membrane was dried in an oven, and its mass W was measured. d The water absorption rate was calculated based on the change in mass of the nanofiber membrane before and after water absorption. Each group consisted of five parallel samples, and the average value was taken. The calculation formula is shown in Formula 1:
[0106]
[0107] Moisture permeability test: The nanofiber membrane was sealed in the mouth of a permeable cup containing deionized water, with the lower surface of the nanofiber membrane in contact with the mouth of the cup. It was placed in a constant temperature and humidity chamber at (37±1)℃ and RH=20%. After a period of time, it was removed and weighed to measure its moisture permeability. Each group consisted of 5 parallel samples, and the average value was taken. The calculation formula is shown in Formula 2:
[0108]
[0109] Where: W1—mass before test (g), W2—mass after test (g), A—effective area of the permeation cup (mm²) 2 T—Test time (h).
[0110] Mechanical property testing: The tensile strength and elongation at break of the nanofiber membrane were determined using a universal tensile strength tester with a clamping distance of 30 mm and a tensile speed of 100 mm / min. The thickness of the nanofiber membrane was measured using a thickness gauge. Before testing, the nanofiber membrane was stored overnight in a constant temperature and humidity chamber at (20±1)℃ and RH=65%. Each group consisted of 5 parallel samples, and the average value of the results was taken.
[0111] The nanofiber membranes obtained in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests according to the above method, and the test results are shown in Table 1.
[0112] Table 1. Performance test results of Examples 1-4 and Comparative Examples 1-3
[0113] sample Water absorption rate (%) <![CDATA[Water vapor transmission rate (g / m 2 / d)]]> Fracture strength (MPa) Elongation at break (%) Example 1 16.4 4182 31.2 320 Example 2 16.9 4260 30.5 296 Example 3 14.3 4075 32.7 345 Example 4 10.7 3183 35.2 397 Comparative Example 1 18.5 4832 15.6 213 Comparative Example 2 26.1 5021 8.3 147 Comparative Example 3 17.2 4213 27.8 291
[0114] As shown in Table 1, although the water absorption and moisture permeability are higher when polycaprolactone, aqueous polyurethane, or ethanol vapor treatment are removed, the mechanical properties all decrease to varying degrees, which is not conducive to applications in fields with high mechanical performance requirements and narrows the application range of nanofiber membranes. In contrast, the nanofiber membranes prepared in Examples 1-4 of this invention exhibit excellent water absorption, moisture permeability, and mechanical properties. Furthermore, since both polycaprolactone and sericin are biodegradable materials, no acidic substances affecting biocompatibility are generated during the degradation process, enabling the nanofiber membranes prepared in this invention to also possess excellent biocompatibility.
[0115] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning, characterized in that: The following steps are involved: (1) mixing polypropylene glycol, dimethylol propionic acid, isophorone diisocyanate and stannous octoate to perform a first reaction; cooling, adding triethylamine to perform a neutralization reaction; then adding water to perform a first emulsification to obtain an aqueous polyurethane; adding a sericin solution to the aqueous polyurethane to perform a second emulsification to obtain an aqueous polyurethane grafted sericin emulsion; (2) mixing polycaprolactone, aqueous polyurethane grafted sericin emulsion and hexafluoroisopropanol to obtain a spinning solution; electrospinning the spinning solution to obtain a composite nanofiber membrane to be treated; (3) treating the composite nanofiber membrane to be treated under ethanol vapor to obtain a waterborne polyurethane grafted sericin composite nanofiber membrane; The method for preparing the sericin solution in step (1) comprises the following steps: The crushed silk cocoons are mixed with anhydrous sodium carbonate solution to perform degumming to obtain a precursor solution; the precursor solution is dialyzed to obtain sericin; the sericin is mixed with water to obtain a sericin solution; In step (1), the speed of the first emulsification is 6000-10000 r / min, and the time is 2-4 min; in step (1), the speed of the second emulsification is 4000-6000 r / min, and the time is 1-2 h.
2. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 1, characterized in that: The step (1) comprises the following raw materials in parts by weight: 30-60 parts of polypropylene glycol, 2-5 parts of dihydroxymethylpropionic acid, 20-36 parts of isophorone diisocyanate, 0.1-0.3 parts of stannous octoate, 0.5-3 parts of triethylamine, 100-200 parts of water, and 75-150 parts of sericin solution; the concentration of the sericin solution in step (1) is 15-25wt.%.
3. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 1 or 2, characterized in that: The temperature of the first reaction in step (1) is 75-85°C and the time is 2.5-5h; the temperature of the neutralization reaction in step (1) is 35-40°C and the time is 0.8-1.6h.
4. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 3, characterized in that: The solid content of the aqueous polyurethane grafted sericin emulsion in step (1) is 20-45%.
5. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 1, characterized in that: The preparation method of polycaprolactone in step (2) comprises the following steps: Tetrahydrofuran, small molecule monohydric alcohol, diphenyl phosphate solution and caprolactone are mixed, and polymerization reaction is carried out under protective atmosphere to obtain polycaprolactone.
6. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 5, characterized in that: The small molecule monohydric alcohol is n-propanol or n-butanol.
7. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 1 or 5, characterized in that: In step (2), the mass volume ratio of the polycaprolactone, the aqueous polyurethane grafted sericin emulsion and the hexafluoroisopropanol is 1 g: 5-12 g: 20 mL.
8. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 1, characterized in that: The parameters of the electrospinning in step (2) are: a receiving distance of 15 to 20 cm, a pinhole inner diameter of 0.8 to 1.2 mm, a solution flow rate of 0.4 to 0.6 mL / h, and a voltage of 15 to 20 kV.
9. The method for preparing a waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning according to claim 1 or 8, characterized in that: The treatment time under ethanol vapor in step (3) is 0.4 to 1 h, and the concentration of ethanol vapor in step (3) is 70 to 85 wt.%.
10. A waterborne polyurethane grafted sericin composite nanofiber membrane based on electrospinning, characterized in that: The electrospinning-based aqueous polyurethane grafted sericin composite nanofiber membrane is prepared by the preparation method of the electrospinning-based aqueous polyurethane grafted sericin composite nanofiber membrane according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of sericin / polyvinyl alcohol composite nano-fiber
CN105734713A
Polycaprolactone and preparation method thereof
CN117659360A
Method for preparing composite fiber membrane with high ultraviolet light absorption capacity based on electrostatic spinning
CN118007273A
Polyurethane elastic yarn and method for producing the same
JP2006169678A